2013
DOI: 10.1088/0004-637x/766/1/59
|View full text |Cite
|
Sign up to set email alerts
|

Gama/H-Atlas: The Dust Opacity–stellar Mass Surface Density Relation for Spiral Galaxies

Abstract: We report the discovery of a well-defined correlation between B-band face-on central optical depth due to dust, τ f B , and the stellar mass surface density, µ * , of nearby (z ≤ 0.13) spiral galaxies: log(τ f B ) = 1.12(±0.11) · log µ * M⊙kpc −2 − 8.6(±0.8). This relation was derived from a sample of spiral galaxies taken from the Galaxy and Mass Assembly (GAMA) survey, which were detected in the FIR/submm in the Herschel -ATLAS science demonstration phase field. Using a quantitative analysis of the NUV atten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(99 citation statements)
references
References 111 publications
(132 reference statements)
6
93
0
Order By: Relevance
“…We recommend that for more detailed studies of sizes, an analysis on an object-by-object case should be involved, in conjunction with determinations of disk opacities. We show that self-consistent determinations of both intrinsic disk and bulge sizes and dust opacities can be obtained using the library of model SEDs of Popescu et al (2011) or the method of Grootes et al (2013a), since these have been obtained with the same radiative transfer model that was used to derived the corrections presented in this paper. …”
Section: Galaxies With De Vaucouleurs Bulgesmentioning
confidence: 97%
See 2 more Smart Citations
“…We recommend that for more detailed studies of sizes, an analysis on an object-by-object case should be involved, in conjunction with determinations of disk opacities. We show that self-consistent determinations of both intrinsic disk and bulge sizes and dust opacities can be obtained using the library of model SEDs of Popescu et al (2011) or the method of Grootes et al (2013a), since these have been obtained with the same radiative transfer model that was used to derived the corrections presented in this paper. …”
Section: Galaxies With De Vaucouleurs Bulgesmentioning
confidence: 97%
“…The use of this approach allows for a self-consistent determination of both intrinsic parameters of galaxies derived from global measurements and structural parameters derived from images. For galaxies without measurements of integrated dust luminosities, the dust opacity can be derived solely from optical data, using the method of Grootes et al (2013a), which was calibrated by using the same radiative transfer model of Popescu et al (2011), again allowing for a self-consistent analysis of both integrated quantities and structural properties.…”
Section: Application: the Inclination Dependence Of Dust Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are consistent with the large f dust variation derived in the present study. The possible temporal and spatial f dust variations would have some implications on some recent observational works, e.g., Eales et al (2012), which have tried to estimate the total amount of cold gas in galaxies by using the continuum dust emission, and Grootes et al (2013), which have revealed correlations between the (middle), and 0 (right). Each small black dot represents each gas particle in the three panels, and the large red square represents the mean f dust and f H 2 in each panel.…”
Section: Radial Gradients Of D and Dust Depletion Levelsmentioning
confidence: 99%
“…(a) I calculated the stellar mass from the photometry (Riechers et al 2013) using the Grasil code. (b) I calculated the gas mass from the L CII luminosity (Venemans et al 2012) using the empirical calibration of Swinbank et al (2012): galaxies Grootes et al 2013), and distant galaxies (Dwek et al 2007;Michałowski et al 2010c,b;Hirashita & Kuo 2011;Mattsson 2011;Mattsson & Andersen 2012;Kuo & Hirashita 2012;Asano et al 2013;Calura et al 2014;Hjorth et al 2014;Rowlands et al 2014;Valiante et al 2014;Nozawa et al 2015). The grain growth timescale is relatively short (a few tens of Myr; Draine 1990Draine , 2009Hirashita 2000Hirashita , 2012Zhukovska et al 2008), which is consistent with very little variation in the metal-to-dust ratios in gamma-ray burst (GRB) and quasar absorbers, as this implies very rapid dust production soon after metal enrichment (Zafar & Watson 2013).…”
Section: Introductionmentioning
confidence: 99%